Development of Website-Based Traditional Games as an Introduction to Local Culture for Early Age Children - Puji Yanti Fauziah; Retna Hidayah; Apri Nuryanto; PH. Pratiwi; Arif Wijayanto; Dwi Ismawati; Nining Purwaningsih (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
This research aims to develop traditional website-based games for early childhood. The research is ADDIE model R&D research. The subjects of this research were 2 expert validators and 30 teachers from 30 PAUD institutions in Indonesia. Data collection techniques use questionnaires.The research results are based on the results of validation by experts with a score. The validation instrument consists of material aspects and also ease of use, the assessment score range uses a Likert scale of 1-4, and the results of the validation carried out regarding the content on the website get a score of 3. 86 means that in terms of material on the website it is suitable for AUD and from the aspect of convenience it gets a score of 3.9 which means very good and easy to use. The research results were based on results from users or from 30 PAUD teachers from 30 PAUD institutions in Indonesia. The score obtained was that learning was in accordance with children's theories, 36.4% answered good and 63.6% very good.